In-vitro investigation of anti-acne properties of Mangifera indica L. kernel extract and its mechanism of action against Propionibacterium acnes. (August 2018) - Poomanee, Worrapan; Chaiyana, Wantida; Mueller, Monika; Viernstein, Helmut; Khunkitti, Watcharee; Leelapornpisid, Pimporn
Abstract: Propionibacterium acnes has been recognized as a main target for medical treatment of acne since this bacterium promotes acne inflammation by inducing upregulation of pro-inflammatory cytokines production, resulting in an accumulation of neutrophils and oxygen-free radicals produced by neutrophils within acne lesion. The aims of this study were to evaluate the biological activities of Mangifera indica kernel extracts grown in Northern Thailand (Kaew-Moragot cultivar), related to anti-acne properties including antimicrobial effect against acne-inducing bacteria together with the first elucidation of the mechanism of action against Propionibacterium acnes, anti-oxidation, and anti-inflammation. The kernels of M. indica, obtained from raw and ripe fruits, were macerated using various solvents. Agar diffusion and broth microdilution methods were performed to investigate the antibacterial activities of the extracts against P. acnes, Staphylococcus aureus, and Staphylococcus epidermidis . The ethanolic fractions exhibited the strongest antimicrobial effect against P. acnes with minimum inhibitory concentration and minimum bactericidal concentration of 1.56 mg/mL and 12.50 mg/mL, respectively. Bactericidal effect against P. acnes of these extracts could be observed after 3 h of incubation from time-kill curve. The chromatograms of high-performance liquid chromatography showed that the extracts existed gallic acid with high total phenolic content. These extracts additionally showed strong free radical scavenging properties on 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and 2, 2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) as well as a notable inhibitory effect on linoleic acid peroxidation, which highly correlated to their antimicrobial effect, total phenolic, and gallic acid contents. The images, studied through using transmission electron microscopy, revealed that the extract certainly disrupted P. acnes cell membrane after exposure for 1 h as well as induced the consequent leakage of cytoplasmic materials. The inhibitory effects of the extracts on IL-8 secretion from LPS-inducing RAW 264.7 cells were also presented. In conclusion, the kernel extracts of raw M. indica fruit were effective against aerobic and anaerobic acne-inducing bacteria particularly P. acnes and exerted antioxidant along with anti-inflammatory activities. Therefore, the extracts might be potential agents for inflammatory acne treatment. However, clinical study is needed for further investigation. Graphical abstract: Image Highlights: Mangifera indica L. kernel extracts were evaluated for their anti-acne properties. The ethanolic fractions showed antibacterial activities against Propionibacterium acnes. TEM indicated that disrupting P. acnes cell membrane was the mechanism of action of the extract. The ethanolic fractions exhibited potent antioxidant properties with reference to gallic acid. The inhibitory effects of the extracts on IL-8 secretion were better than that of gallic acid.